Determinants of Profitability of Black Soldier Fly Farming Enterprise in Kenya - Mutuku, K.V.; Mukhebi, A.W.; Orinda, M.A.; Tanga, C.M. (Journal of Insects as Food and Feed, 2021)
Black soldier fly (BSF) farming is emerging as a new farm enterprise in Kenya poised to provide high-quality and affordable alternative protein sources for animal feed production. Consequently, commercialization and adoption require farmers to understand if the enterprise is economically viable. This study sought to assess the determinants of profitability of the BSF farm enterprise. A census survey was conducted whereby 34 well-established smallholder BSF farmers were interviewed. A double log regression analysis on the determinants of profitability of the BSF farm enterprise was done. The results revealed that 93.6% of the variation in enterprise gross margin was explained by the independent variables. Feed and household size contributed positively and significantly to the enterprise gross margin. Labour was significantly and negatively correlated to the enterprise gross margin. Farm size, gender, level of education, and age of the farmer did not significantly influence the gross margin of the enterprise. Furthermore, the survey showed that a 1% increase in man-hours spent in the BSF farming enterprise would result in a 0.34% reduction in the gross margin while a 1% increase in the usage of the rearing substrate would lead to a 1.38% increase in the gross margin. There is a need for farmers to reduce the man-hours spent in the BSF farms but at the same time increase significantly the utilization of more rearing substrate to improve their profitability. However, a long-term socio-economic impact assessment on the BSF farming enterprise would be valuable to attract investors and interest in the insect production sector for animal feed.
Keywords: Black Soldier Fly; Gross Margin; Enterprise; Profitability